Qos-Reconfigurable Web Services and Compositions for High-Assurance Systems. - Yen, I.-Ling; Hui Ma; Bastani, Farokh B.; Hong Mei (Computer (00189162), 2008)
The article discusses the use of service-oriented architecture (SOA) to achieve reconfigurability of modern adaptive application systems. Reconfigurable systems, the article states, can complement techniques used for service selection which satisfy changing or static system quality-of-system (QoS) requirements. Topics include the satisfaction of mission-specific needs, deriving QoS goals for individual services, and limited sets of alternative services from which one may choose. Also discussed is a rule-based parameterization technique.